Validitas dan Reliabilitas Konstruk Person-Organization Fit di Indonesia - Gianti Gunawan (Universitas Kristen Maranatha, 2020)
Organizational culture is a guideline for employees in performing work. Employees can perform well if employees have the same values ??as organizations. The theory of person-organization fit (Kristof-Brown et al, 2005) explains the degree of compatibility between individual characteristics and the environment, which measured by two dimensions, namely supplementary fit, and complementary fit. Based on this theory, we make a questionnaire consisting of 31 items. This study examined the psychometric quality of person-organization fit scale to obtain a valid and reliable instrument. Validity and reliability tests were carried out using CFA (Confirmatory Factor Analysis) to 460 employees. The loading factor (?) for the supplementary fit dimension and the complementary fit dimension is greater than 0.5, thus indicating the items of the two dimensions are valid. Reliability test shows the value of CR (construct reliability) above 0.7 and VE (variance extracted) above 0.5, so it can be concluded that endogenous constructs have good construct validity and reliability Keywords: person-environment fit, person-organization fit, supplementary fit, complementary fit, confirmatory factor analysis